1994
DOI: 10.1002/ijc.2910570421
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor activity of mycophenolate mofetil against human and mouse tumors in vivo

Abstract: Cultured tumor cell lines, tumor xenografts grown in athymic nude mice, and a murine experimental metastasis model were used to assess the in vitro and in vivo anti-tumor activity of the potent IMP dehydrogenase (IMPDH) inhibitor, mycophenolic acid (MPA), and its morpholinoethyl ester pro-drug, mycophenolate mofetil (MM). The growth of all the cell lines tested was inhibited by MPA in vitro, with EC50 values ranging from less than 0.1 microM to 3.9 microM. Mice were monitored for s.c. tumor outgrowth in the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 15 publications
3
46
0
2
Order By: Relevance
“…However, not all immunosuppressants necessarily promote cancer development. While mycophenolate mofetil has some capacity to reduce tumor cell proliferation (15,16), rapamycin exhibits impressive inhibitory effects on cancer development. Rapamycin inhibits angiogenesis and tumor cell proliferation (15,17,18), leading to impaired inoculated tumor growth in mice and de novo tumor development in a p53-null mice (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all immunosuppressants necessarily promote cancer development. While mycophenolate mofetil has some capacity to reduce tumor cell proliferation (15,16), rapamycin exhibits impressive inhibitory effects on cancer development. Rapamycin inhibits angiogenesis and tumor cell proliferation (15,17,18), leading to impaired inoculated tumor growth in mice and de novo tumor development in a p53-null mice (19).…”
Section: Introductionmentioning
confidence: 99%
“…While mycophenolate mofetil has some capacity to reduce tumor cell proliferation (15,16), rapamycin exhibits impressive inhibitory effects on cancer development. Rapamycin inhibits angiogenesis and tumor cell proliferation (15,17,18), leading to impaired inoculated tumor growth in mice and de novo tumor development in a p53-null mice (19). Interestingly, azathioprine-treated transplant recipients have more mutant p53-overexpressing cell clusters in precursor skin lesions than immunocompetent patients with skin carcinomas (20); this finding contrasts with results in rapamycin-fed mice that develop fewer mut-p53 cell clusters than control mice (21).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that administration of IMPDH inhibitors to cultured cells results in inhibition of DNA synthesis (11) and cellcycle arrest at the G1-S boundary (12,13). Inhibitors of IMPDH have also been shown to possess antineoplastic (14,15), antiviral (16), antiparasitic (17), and immunosuppressive (18,19) activities, and to induce Inosine 5′-monophosphate dehydrogenase (IMPDH) is the rate-limiting enzyme in the de novo synthesis of guanine nucleotides, which are also synthesized from guanine by a salvage reaction catalyzed by the X chromosome-linked enzyme hypoxanthine-guanine phosphoribosyltransferase (HPRT). Since inhibitors of IMPDH are in clinical use as immunosuppressive agents, we have examined the consequences of knocking out the IMPDH type II enzyme by gene targeting in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Cells were incubated overnight to attach to the bottom of the wells, and then treated with serials dilutions of MPA (1,5,10,15,20,25 and 30 μg/mL). Cell viability was analyzed by adding 5 mg/mL MTT (Sigma-Aldrich) and 150 μL DMSO.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Mycophenolic acid (MPA) acts as a nonnucleoside, noncompetitive, reversible inhibitor of IMPDH with fivefold higher potency of inhibiting IMPDH2 than IMPDH1. It has been reported to be able to inhibit cancer cell proliferation and induce apoptosis in several experimental models of human solid tumors and hematological malignancies by depleting guanine nucleotide pools (5,(8)(9)(10).…”
mentioning
confidence: 99%